Gastrointestinal Manifestations in COVID-19 Infection and Its Practical Applications - Mandal, Amrendra (Cureus, 2020)
The latest novel coronavirus (COVID-19) outbreak, which emerged in December 2019 in Wuhan, Hubei, China, is a significant cause of the pandemic. This outbreak is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and is also commonly known as COVID-19. A typical symptom includes cough and fever, but a considerable number of patients can manifest gastrointestinal (GI) symptoms, including diarrhea, which can be the initial presentations and may or may not present with respiratory symptoms or fever. COVID-19 virus may be present in stool samples of patients infected with COVID-19, and angiotensin-converting enzyme 2 (ACE2) is a receptor for this virus, which is substantially present in GI epithelial cells. The wide availability of this receptor facilitates COVID-19 infection to be proactive and multiply in the GI tract. Although no antiviral treatments have been approved, several approaches have been proposed, and at present, optimized supportive care remains the mainstay of therapy. Elective endoscopic procedures should be delayed, but the urgent procedures should be performed as indicated. Due to the rapidly evolving data on COVID-19, it is difficult to keep up with the outpouring of information. We reviewed the mechanisms, clinical manifestation, impact on pre-existing liver diseases, and recommendations endorsed by the several GI societies for the management and prevention of its transmission.